Dampak Pemilihan Kepala Daerah Kota Palembang Tahun 2024 Terhadap Pencemaran Lingkungan Di Kota Palembang - Ilham Azis; Ryllian Chandra Eka Viana; Ibrahim Mifthafariz Mirza (CV. ITTC INDONESIA, 2025)
The Regional Head Election (Pilkada) is a vital form of local democratic participation; however, its implementation often generates environmental issues. This study aims to analyze the environmental impact of the 2024 Palembang mayoral election, particularly those caused by campaign activities such as the installation of campaign props, distribution of promotional materials, and mass gatherings. A qualitative approach was employed, using data collected through in-depth interviews, documentation, and literature review. The findings reveal a significant increase in waste volume and visual pollution during the campaign period, especially due to the placement of campaign materials on trees, electric poles, and public spaces in violation of regulations. Additionally, weak law enforcement and a lack of environmental awareness among political actors were identified as key factors exacerbating the situation. The study indicates that although the Pilkada is a democratic process, it often disregards environmental sustainability. This research recommends stricter regulations, an integrated waste management system for campaign activities, and greater community involvement in environmental oversight during elections.